TINGKAT KEPUASAN MASYARAKAT TERHADAP PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA (BSPS) (STUDI KASUS: KECAMATAN JATI AGUNG, KABUPATEN LAMPUNG SELATAN) - Ruri Nastasiya Sari; Bambang Utoyo Sutiyoso; Mia Ermawati (Lembaga Penelitian, Pengabdian Masyarakat, dan Penjaminan Mutu (LP3) ITERA, 2022)
The problem of uninhabitable houses must get more special handling in order to create a prosperous community life. The Self-Help Housing Stimulant Assistance Program (BSPS) is a government program in providing facilities for low-income households to have decent housing. The provision of services can affect the level of satisfaction of the receiving community, because the level of community satisfaction can measure the success of a service or product provided by the government. (Case Study: Jati Agung District, South Lampung Regency) with the aim of knowing the level of community satisfaction with the quality of services provided in the BSPS program. The analysis used is descriptive qualitative in the form of interviews and documentation in this study using three RLH criteria, namely building safety, adequacy of space or minimum area, and health. The results of the study show that there is a conformity between the RLH criteria that have been built with the BSPS program criteria so that there is satisfaction felt by the community because the suitability is in accordance with what is expected and also because of the good service to create houses with livable conditions and improve people's lives towards a more good.